2006
DOI: 10.1001/archotol.132.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Selective Neck Dissection for Node-Positive Necks in Patients With Head and Neck Squamous Cell Carcinoma

Abstract: To evaluate the regional recurrence (RR) rate in a consecutive series of patients with node-positive head and neck squamous cell carcinoma (N ϩ HNSCC) who underwent selective neck dissection (SND) as part of their treatment in a single institution. Design: Retrospective case series with 2 years of follow-up. Setting: Tertiary care university hospital. Patients: One hundred ninety-one patients with N ϩ HNSCC underwent 256 neck dissections (NDs) between 1999 and 2002. Of these, 17 had unilateral SNDs and 11 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The guidelines committee follow the recommendations of the AHNS's Committee for Neck Dissection Classification in eschewing the terms "radical neck dissection" and "modified radical neck dissection." [32][33][34][35] It follows that the NCCN guidelines do note that selective neck dissection may be used for these patients with consideration for adjuvant radiotherapy or chemoradiotherapy (as indicated elsewhere in the guidelines). They suggest that the term "comprehensive neck dissection" be utilized to describe procedures that remove levels I to V, regardless of any other structures (ie, sternocleidomastoid muscle, internal jugular vein, and spinal accessory nerve) that may be removed with the node-bearing tissue.…”
Section: Neck Dissection: Classification and Indicationsmentioning
confidence: 99%
“…The guidelines committee follow the recommendations of the AHNS's Committee for Neck Dissection Classification in eschewing the terms "radical neck dissection" and "modified radical neck dissection." [32][33][34][35] It follows that the NCCN guidelines do note that selective neck dissection may be used for these patients with consideration for adjuvant radiotherapy or chemoradiotherapy (as indicated elsewhere in the guidelines). They suggest that the term "comprehensive neck dissection" be utilized to describe procedures that remove levels I to V, regardless of any other structures (ie, sternocleidomastoid muscle, internal jugular vein, and spinal accessory nerve) that may be removed with the node-bearing tissue.…”
Section: Neck Dissection: Classification and Indicationsmentioning
confidence: 99%
“…The authors of these reports advocating SND for node‐positive disease have concluded that SND is a reasonable approach; their reported regional failure rates after SND for node‐positive disease have varied from 5.7% in the series by Anderson et al5 to as high as 29% in the series by Spiro et al6 This range (5.7%–29% neck recurrence) occurred even with the use of postoperative radiation 5, 6. A number of confounding issues exist in these studies, including 1) evaluation of multiple regions for the primary site (i.e., oral cavity, pharynx, and larynx); 2) variability in the number of nodal levels dissected within reports and between reports; 3) inconsistency in the indications for adjuvant postoperative radiation within and between reports; 4) retrospective analysis in almost all of the studies; and 5) local failure at the primary site (or no discussion of outcomes at the primary site), which begs the question of whether regional recurrence was related to inadequacy of the SND or to failure or inadequacy of the primary oropharyngeal squamous cell carcinoma (OPSCC) resection 7, 8. Finally, none of the reports in the literature have discussed the use of postoperative concurrent chemoradiation following SND.…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen patients had an NR, of whom 15 had been treated by CND and 4 by SND, with an NR rate of 17.2 and 5.8% in CND and SND, respectively. Santos et al [21] reported a series of 28 patients with node-positive H&N squamous carcinoma submitted to 34 SND and 5 RND. NRs occurred in 4 SND and 2 RND.…”
Section: Discussionmentioning
confidence: 99%